Oral Health Inequalities among Indigenous and Non-Indigenous Children. (July 2021) - Haag, D.; Schuch, H.; Ha, D.; Do, L.; Jamieson, L.
Introduction: Our ability to address child oral health inequalities would be greatly facilitated by a more nuanced understanding of whether underlying disease experience or treatment opportunities account for a larger share of differences between social groups. This is particularly relevant in the context of population subgroups who are socially marginalized, such as Australia's Indigenous population. The decayed, missing, and filled (dmf) surfaces index is at once a reflection of dental caries experience (d) and its management (m and f). Objectives: To 1) describe socioeconomic inequalities in dental caries experience and its management among Indigenous and non-Indigenous children and 2) compare these inequalities using absolute and relative measures. Methods: Data were from the Australian National Child Oral Health Study 2012–2014. Absolute and relative income inequalities were assessed for overall dmfs and its individual components (ds, ms, fs) using adjusted means and health disparity indices (Slope Index of Inequality [SII] and Relative Index of Inequality [RII]). Results: Mean dmfs among Indigenous children aged 5 to 10 y was 6.4 (95% confidence interval [CI], 5.4–7.4), ranging from 2.3 in the highest to 9.1 in the lowest income group. Mean dmfs among non-Indigenous children was 2.9 (95% CI, 2.8–3.1), ranging from 1.9 in the highest to 4.2 in the lowest income group. Age- and gender-adjusted social gradients for Indigenous children were evident across all dmfs components but were particularly notable for ds (SII = −4.6, RII = −1.7) and fs (SII = −3.2, RII = −1.5). The social gradients for non-Indigenous children were much lower in magnitude: ds (SII = −1.8, RII = −1.6) and fs (SII = −0.7, RII = −0.5). Conclusion: Our findings suggest that socioeconomic disadvantage may translate into both higher disease experience and increased use of dental services for both Indigenous and non-Indigenous groups, with the social gradients being much more amplified among Indigenous children. Knowledge Transfer Statement: The findings of this study demonstrate the magnitude of disparities in dental caries among children by population groups in Australia. Our results suggest that the relationship between socioeconomic disadvantage and poor oral health is more deleterious among Indigenous than non-Indigenous children. Tackling upstream determinants of health might not only affect population patterns of health and disease but also mitigate the overwhelming racial inequalities in oral health between Indigenous and non-Indigenous Australians.